Species Richness and Diversity of Klawalu Mangrove, Doberai Peninsula, Indonesian New Guinea - Anike Asmuruf; Yolanda Holle; Agustinus Murdjoko; Nithanel M.H. Benu; Dony A. Djitmau (Annals of Silvicultural Research)
Mangrove plays an important role in the coastal area in particular as an ecological service, yet ecosystem cover has been declining for decades. This research was designed to find out the vegetation diversity of mangroves in Klawalu, Doberai Peninsula, Indonesian New Guinea.  The 30 nested plots were located in three locations as the representation of mangrove fringe, intermediate, and landward zone, consecutively.  This study revealed that mangrove forest consists of 21 species classified as the main structure and 9 species as mangrove associates. In general, the mangrove forest is able to regenerate naturally where fecundity establishment can be seen by the number of small individuals.  The species diversity and the number of individuals from the edge to the inland increase resulting from tidal factors affecting the seed dispersal and sapling establishment.  Practically, government intervention is needed to strengthen the status of the area as a protected area by means of regional regulations to manage sustainably the mangrove.